UJI AKTIVITAS ANTIINFLAMASI DARI EKSTRAK METANOL DAUN KENITU (Chrysopyllum cainito L.) SECARA IN VITRO - Nur Hidayah; Chairul Saleh; Djihan Ryn Pratiwi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Antiinflammatory activity tests of extract and fractions of kenitu Leaves (Chrysopyllum cainito L) in vitro were carried out. This research aimed to determine the anti-inflammatory activity of crude extract methanol of kenitu leave with protein denaturation inhibition method by using BSA (Bovine serum albumin). Diclofenac sodium was used as positive control and the negative control used the appropriate solvent. Based on phytochemical screening test, methanol extracts are known to contain secondary metabolites including flavonoids, alkaloids and phenolics. The results of the anti-inflammatory activity test of methanol extract have moderate anti-inflammatory potential with an IC50 value of 196,29 ppm. Keywords: Chrysopyllum cainito L, Secondary metabolites, Anti-inflammatory, 50% inhibition concentration.